The influence of price-related point-of-sale promotions on bottle shop purchases of young adults - Jones, S.; Barrie, L.; Gregory, P.; Allsop, Steve; Chikritzhs, Tanya (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims.To investigate the impact of point-of-sale promotions on product choice, brand choice and purchase quantity of young adults purchasing alcohol for off-premise consumption in Australia. Design and Methods. A crosssectional interviewer-completed survey conducted at 24 bottle shops (liquor stores), 12 each in the capital cities of Sydney, NewSouth Wales and Perth, Western Australia. Participants were 509 adults (18 and over) exiting bottle shops having purchased alcohol. Results.When prompted,26.5% indicated that there was a special offer, price discount, or special promotion connected with a product that they had purchased. Those who participated in point-of-sale promotions purchased a greater quantity of alcohol than those who did not participate: ready to drink, an average of 11.5 standard drinks (SD) compared with an averageof 8.9 SD (t = 1.320, P = 0.190); beer, an average of 26.8 SD compared with an average of 16.4 SD; wine, an average of 16.1 SD compared with an average of 13.8 SD (t = 0.924, P = 0.357). Discussion and Conclusions. Participation in point-of-sale promotions may be associated with increased purchase quantities, not solely shifting between brands.There is a needfor further research to explore changes in purchase and consumption patterns as a result of the availability of price-based promotions.The results of this study, combined with previous research, suggest that regulators—and marketers—should consider the immediate and cumulative effect of point-of-sale promotions on drinking patterns, particularly those of younger drinkers.